Effect of Nanoclay on Thermomechanical Behaviour of Graphene Oxide/Polymer Composites. (2017) - Panwar, Vinay; Chattree, Ananya; Pal, Kaushik
Abstract: This work explores the effectiveness of nanoclay (NC) as compatibilizer in graphene oxide (GO) reinforced Nylon66 (N66) nanocomposites, prepared through melt mixing technique. Different composites have been prepared with varying concentration of NC to determine its optimum content for an effective improvement in thermomechanical properties of GO/N66 composites. XRD curves have shown that properly exfoliated nanocomposites have been synthesized with the use of NC as secondary filler. FTIR has been used to confirm presence of different elements and the nature of interaction between N66 and fillers. Thermogravimetric analysis have shown that the effect of GO and NC on thermal decomposition behaviour of GO/N66 composites is insignificant. The mechanical and thermomechanical properties of these composites have been studied with the help of tensile tests, flexural tests and dynamic mechanical analysis. The incorporation of 2 wt% NC in GO-N66 nanocomposite shows most significant improvement in its tensile and flexural strength (93.2% and 121.5%, respectively). DMA studies revealed improvement in storage modulus of GO-NC reinforced hybrid composites. Glass transition (Tg ) of 2NC-GO-N66 nanocomposite have been noticed to improve by 12.5%. FESEM images have shown that agglomeration of nanoparticles takes place when the content of NC reaches 3 wt%. This provides the reason for poor mechanical and thermomechanical properties of the composite having NC more than 2 wt%.